Impact of COVID-19 Pandemic on Organization of Religious Behaviour in Different Christian Denominations in Poland - Sulkowski, Lukasz; Ignatowski, Grzegorz (Religions (Basel, Switzerland ), 2020)
Any pandemic disorganizes the life of wider society. One of the manifestations of social activity is religious life. Despite progressing secularization, both religion, churches, and denominational associations have an impact on individual ethical choices and business decisions. This is true especially in Poland, where over 90 percent of the citizens declare affiliation with some religion, mostly Christian. The purpose of the present article is to demonstrate what activities are undertaken by churches in Poland at the time of the COVID-19 pandemic, and what differences there are in their organization of religious life. In order to achieve the set goal, qualitative methods were implemented in the research. As part of the qualitative paradigm, in-depth individual interviews were used, involving individuals responsible for organizing religious life at the parish or congregation level. The interviewees were clergymen from the most important denominations, ranging from Catholic and Orthodox to broadly understood Protestant denominations. The paper contains a review of relevant literature. It presents the results and discussion of qualitative research, and it also indicates the research limitations. The study reveals that individual churches have limited (Catholic and Orthodox) or totally suspended (Protestants) their religious life in the actual community-based dimension. The decisions made by the clergymen, regardless of their personal views, resulted from the assumed ecclesiology and tradition. While changing the organization of religious life, the churches maintained contact with the believers in various ways, using modern technologies and access to public media in this regard. Although the churches are not changing their doctrinal positions, they declare different forms of cooperation.